Effects of filler components on mechanical properties and machinability characteristic of palm oil based wax - Mohd Faizal Hamid (School of Manufacturing Engineering, 2011)
This thesis presents, a comprehensive study on the blends of palm oil based wax with filler components such as linear low polyethylene (LLDPE) and high density polyethylene (HDPE). The work targets the development of cheap industrial wax made from palm oil.